PENINGKATAN KETERAMPILAN MENULIS KARYA SASTRA DAN PENGELOLAAN MAJALAH SASTRA BAGI MAHASISWA PROGRAM STUDI PENDIDlKAN BAHASA JA WA MELALUI MAGANG KEWlRAUSAHAAN - Suwardi, Suwardi; Widayat, Afendy (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2003)
Program  of  Entrepreneurship  Volunteer  is  aimed  to  prepare  the  graduate  ofJavanese Language  study Program of FBS UNY Yogyakarta to compete in the job field., T,o achieve marketable graduates, the study Program offers cooperation with partners to prepare.the students in writing literary works, managing studios, and literary magazines., .       , ' Process' M  volunteering is perfomed by giving provisions in the partners'  places.Joining students are chosen from Sanggar Sastra Lecture and selected based on talents ang motivations. The indicators of success for each student are making a title for short strory, jagading   lelembut,  and geguritan,   and able to make a planning of studio establishment ang literary magazine.The participants were  16. However, the active persons were  11. After following.volunteering process, there were eight short stories to publish. Moreover, it is better since, there was a short story being published by mass media entitled Dak  Coreng  Mangsi  Abang(Ari Yuliani). Of  some  geguritaris made  by the  students,  almost  all  of  them  can be. published in mass media. There are 15 titles of geguritan recommended to publish, that it can be sent to mass media However, six titles need corrections. Some of the geguritans published in Sempulur   magazine are Sudra,  Sempati    written by Agus Yuana Dirgantara and Sepi witten by Sri Suranti. Then, in the category og jagading lelembut there was seven titles and all of them are proper to publish. In other case, the effort of studio management and literary magazine  establishment  are still  in the  form of proposal  consulted to the partners.Key words:  written  skills, literary  magazine, and  entrepreneurship  volunteer.